2014
DOI: 10.1039/c4ta00665h
|View full text |Cite
|
Sign up to set email alerts
|

High performance of microtubular solid oxide fuel cells using Nd2NiO4+δ-based composite cathodes

Abstract: Cathodes of porous YSZ supports infiltrated with Nd2NiO4+δ nanoparticles are offered as an alternative solution for IT-SOFC cathodes, presenting maximum power densities of 0.4 W cm−2 at 600 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…The most significant change is the decrease of the LF contribution for the CY cell under negative polarization (SOEC conditions), as a consequence of the optimized gas diffusion within the Ni-YSZ support. Positive impacts of using calcined YSZ in developing a porous YSZ microstructure for conversion to an anode or cathode upon infiltration has been previously shown by the authors1415161819212728. When cell infiltration for the purpose of improving the catalytic activity or the electronic/ionic conductivity (or both) of the anode is planned, an anode with larger pore size and higher porosity (~50%) than TY is desirable (due to pore clogging during infiltration).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The most significant change is the decrease of the LF contribution for the CY cell under negative polarization (SOEC conditions), as a consequence of the optimized gas diffusion within the Ni-YSZ support. Positive impacts of using calcined YSZ in developing a porous YSZ microstructure for conversion to an anode or cathode upon infiltration has been previously shown by the authors1415161819212728. When cell infiltration for the purpose of improving the catalytic activity or the electronic/ionic conductivity (or both) of the anode is planned, an anode with larger pore size and higher porosity (~50%) than TY is desirable (due to pore clogging during infiltration).…”
Section: Resultsmentioning
confidence: 97%
“…The effectiveness of using calcined YSZ in the development of a porous structure for infiltration of nickel1415 or LSBT16 anodes as well as LSM1718 or Nd nickelate19 cathodes has been previously shown by the authors. Despite many studies on the effect of nickel particle size and content on anode microstructure and thus performance, there is a lack of information in the literature regarding the effect of using processed YSZ in the conventional nickel-YSZ anode on electrochemical performance.…”
mentioning
confidence: 92%
“…Furthermore, the large and irregular pores of the 430 L substrate enhance steam absorption and diffusion. It can be observed that the performance in SOEC mode is significantly better than in SOFC mode, probably due to the hyperstoichiometry of the NNO Ruddlesden-Popper phases leading to fast oxygen diffusion through bulk the materials and rapid exchange kinetics [14,21,22]. In addition the Nd 2 O 3 could play a significant role at the oxygen electrode as its presence may hinder the sintering of NNO particles, and thus maintaining a large surface area.…”
Section: Resultsmentioning
confidence: 94%
“…1(a). Although the Nd 2 O 3 phase is observed, previous studies have shown that it does not affect the cathode performance [14,15].…”
Section: Methodsmentioning
confidence: 97%
“…Fluctuations in current are mainly due to imperfect current collector attachment especially at the anode side and coarsening of the electrode particles. 43 After four days, some slight variation was observed but there was no significant decrease in the performance compared to the start of the test. Where, E ao = Activation energy due to ohmic contribution, and E ap = Activation energy due to polarization contribution.…”
mentioning
confidence: 99%